THE ROLE OF DIGITAL FORENSICS IN THE PRELIMINARY INVESTIGATION - Astria Santa Natalia Mantiri; Elvis Sumanti (Klabat Accounting Review, 2022)
In this era, technological developments have a significant influence in business. However, many taxpayers abuse the use of technology to commit fraud. Therefore, there needs to be a system that can filter and detect data of taxpayers who commit fraud. This research is conducted to analyze digital forensics' role in dealing with fraud and to determine the critical success factors that support the digital forensics in detecting fraud. This study uses qualitative reasearch where the author wanted to find out the role of Digital Forensics in the Preliminary Evidence Examination by interviewing the digital forensic officer in one of Tax Offices in Indonesia. The result proves that the role of digital forensics in the preliminary Investigation is crucial. The management and development of digital data can be carried out effectively with valid evidence through Digital Forensic activities (UU ITE). The skill of Digital Forensics officer in using programs to process data is essential in getting evidence. Taxpayer participation is also important in gathering evidence. The amount of digital evidence collected will be used through analysis and development by using chain of custody method, where this method can ensure the integrity of the data processed to convince the court in making decisions. Keywords: Digital Forensic, Preliminary Investigation, Tax Audit, Tax Fraud